TPACK SEBAGAI KATALIS PENINGKATAN HOTS PEMBELAJARAN PAI (STUDI KASUS SD KOTA BANDAR LAMPUNG) - Misbah Nurdin; Bambang Dri Anggoro; Chairul Amriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the implementation of Islamic Religious Education (PAI) learning based on TPACK (Technological Pedagogical Content Knowledge) to improve Higher Order Thinking Skills (HOTS) of elementary school students in Rajabasa District, Bandar Lampung. Using a qualitative approach with a comparative case study design, this study analyzed three schools: SD Al-Kautsar, SD Global Madani, and SDN 2 Rajabasa. The results showed significant variations in PAI teachers' mastery of TPACK. Teachers demonstrated strengths in Content Knowledge (CK) and Pedagogical Content Knowledge (PCK), but faced challenges in domains involving technology (TK, TCK, TPK) and the holistic integration of TPACK. The TPACK implementation strategies found varied: SD Al-Kautsar adopted the "Islamic Digital Learning Ecosystem" model, SD Global Madani adopted the "Hybrid Learning" approach, and SDN 2 Rajabasa implemented the "Low-Tech High-Impact" strategy. The main challenges include limited infrastructure, difficulty integrating technology without reducing the depth of religious content, and cultural resistance. Innovative solutions implemented include the use of open source alternatives, a Bring Your Own Device (BYOD) policy, and a Digital Islamic Literacy for Parents program. This research also produced novelties such as "Islamic Digital Pedagogy" (IDP), the concept of "Adaptive TPACK," "HOTS-Islamic Values ​​Integration Matrix," and "Digital Spiritual Intelligence" (DSI), which demonstrate students' ability to integrate digital intelligence with spirituality. This research confirms that the implementation of adaptive and creative TPACK is effective in increasing HOTS and promoting religious values ​​in Islamic Religious Education learning in the digital era.